Interpretation of the Electrocardiogram (Res Medica, 2014)
Accurate interpretation of an E .C .G. may provide valuable information on the assessment of a patient’s cardiovascular system.  Students, both under-graduate and post-graduate, may have to interpret an E.C.G. in the course of their daily ward duties or during a clinical examination and in this article emphasis is placed on the main diagnostic features of some of the more common E.C.G. abnormalities.  Numerous books are available for more advanced study.The E.C.G. is particularly useful in the diagnosis of cardiac rhythm and myocardial infarction.  It may reveal evidence of conduction defect, hypertrophy of the myocardium or pericarditis and may also indicate therapeutic response in certain electrolyte disturbances.  On the other hand, non-specific E.C.G. changes are common.